Decision‐Making in Local Context: Expertise, Experience, and the Importance of Neighbours in Farmers' Insect Pest Management. Issue 1 (2nd October 2019) - Noy, Shiri; Jabbour, Randa
Abstract: Drawing on data from four focus groups with alfalfa farmers conducted in Spring 2014 and 2015 in four counties in Wyoming, USA, we analyse how farmers make decisions about insect pest management. Our generative focus group data allow us to examine how farmers frame and value different sources of information and why and when they rely on them. Our results reveal that in order to be useful, expert information needed to be local and to consider the complex realities of farming. Neighbours, especially those with deep roots in the community, were seen as valuable and trusted sources of information. Chemical companies and co‐op representatives, on the other hand, received more mixed treatment. We describe the dimensions by which growers categorise information: relevancy, accuracy, locality, and diagnostic/prognostic. Our results underscore the reflexive nature and motivation for farmers' evaluation of information and advice about insect pests.